Membangun Kepribadian Qur’ani melalui Metode Terpadu ‘Ilman wa Ruuhan (Studi SDIT Nurul Izzah Kecamatan Gurah Kabupaten Kediri) - Khoiriyati, Anti; Khainuddin, Khainuddin; Soimah, Zakiyatus (LPTK UIN Syekh Wasil Kediri, 2025)
This study aims to explore efforts to build a Qur'anic personality through the Qur'an learning method. The basis of this study is the moral decadence that is currently rampant. The presence of the Qur'an as a guideline for good moral order is often underestimated. Many Muslims are able to read the Qur'an but do not practice it. This article is based on qualitative field research with a case study type. The methods used to collect data in this study are interviews, observations and documentation. This study produces information that there are twelve indicators of Qur'anic personality that have been formed. The twelve indicators consist of a patient soul, a willing soul, a trustworthy soul, a grateful soul, a brave soul, an honest soul, a generous soul, a repentant soul, a pious soul, a ihsan soul, a consistent soul and a happy soul. This effort was made because the Qur'anic learning method includes the formation of Qur'anic personality in it. The supporting factors for efforts to form Qur'anic personality consist of serious teacher efforts in teaching, school management, competent teachers, a positive environment and adequate facilities and infrastructure. While the inhibiting factors consist of the lack of interest of students in learning the Qur'an and practicing it, poor school management, incompetent teachers, a negative environment and inadequate facilities and infrastructure. The results of this effort have a much better impact, consisting of having high empathy for others, having noble morals, a sense of responsibility, discipline, improving the quality of education and playing an active role in building a better society.